Reproductive health needs of HIV serodiscordant couples: a systematic review - Motaharinezhad, Mohadese; Yousefi, Zahra; Rostami, Sahar; Goli, Shahrbanoo; Keramat, Afsaneh (Frontiers in Public Health, 2024)
Objectives HIV is closely linked to reproductive and sexual health. HIV Serodiscordant couples face significant social, reproductive, and sexual challenges. This systematic review aimed to identify their reproductive health needs. Methods A comprehensive literature search was conducted across six databases: Scopus, PubMed, Web of Science, Google Scholar, Magiran, and Iranmedex. No date restrictions were applied, and only English-language articles published before February 21, 2023, were included. We also searched the grey literature and conducted forward/backward citation searches. Results From an initial 758 articles, 18 met the inclusion criteria. Studies were qualitative (n = 10) and quantitative (n = 8). Key reproductive health needs included (1) childbearing intention, (2) HIV serodiscordance and sexuality, (3) psychological and social support, (4) training and consultation services, (5) access to reliable information, and (6) focused training for healthcare providers. Conclusion HIV-discordant couples face various reproductive health challenges. Implementing comprehensive guidelines for reproductive and sexual health, rehabilitation, and fertility planning is crucial to improving their quality of life and health. Systematic review registration https://www.crd.york.ac.uk/prospero/, identifier CRD42023393567.